Developing Islamic Context-Based Learning Materials in Increasing Students’ Mathematical Understanding - Ulpah, Maria; Novikasari, Ifada (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
Learning material is an important part of the implementation of learning, so teachers should be able to design, arrange, and develop their learning material. There are a lot of mathematics learning materials on the market but they are still rarely integrated with Islamic studies. Therefore, the purpose of this study is to develop Islamic context-based learning material to increase students' mathematical understanding. This study is research and development using the PPE model which consists of three stages, namely planning, production, and evaluation. The data collecting techniques used are tested to find out the students' mathematical understanding and questionnaire to find out expert's assessment. The data is analyzed quantitatively using descriptive data analysis techniques. The data obtained from the questionnaire is quantified to get results in the form of percentages to find out the results of the questionnaire from the validation of the learning material experts. The results showed that Islamic context-based learning material has fulfilled the requirements to be considered feasible to be used in the learning process and is feasible to be used as learning support to increase students' mathematical understanding.